2001
DOI: 10.1067/mva.2001.114812
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open subfascial division of incompetent perforating veins in the treatment of venous leg ulceration: Long-term follow-up

Abstract: The long-term follow-up results of the endoscopic division of perforating veins are comparable with those of the open division of perforating veins (modified Linton procedure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 17 publications
2
56
0
8
Order By: Relevance
“…Since its first description by Hauer in the 1980s, 1) SEPS has been accepted as an improved treatment modality in the surgical treatment of perforating vein insufficiency, particularly in cases with advanced skin changes. SEPS is performed in some facilities in North America [2][3][4][5] and Europe [6][7][8][9][10] as a component of the comprehensive treatment program for venous insufficiency. These previous studies presented favorable results with SEPS.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description by Hauer in the 1980s, 1) SEPS has been accepted as an improved treatment modality in the surgical treatment of perforating vein insufficiency, particularly in cases with advanced skin changes. SEPS is performed in some facilities in North America [2][3][4][5] and Europe [6][7][8][9][10] as a component of the comprehensive treatment program for venous insufficiency. These previous studies presented favorable results with SEPS.…”
Section: Introductionmentioning
confidence: 99%
“…Published evidence indicates good clinical and symptomatic improvement with an ulcer healing rate of over 80%. [39][40][41] At long-term follow-up, ulcer healing and recurrence rates are comparable to open surgery. 41 Limbs with post-thrombotic insufficiency have poorer outcomes.…”
Section: Subfascial Endoscopic Perforator Vein Surgery (Seps)mentioning
confidence: 72%
“…[39][40][41] At long-term follow-up, ulcer healing and recurrence rates are comparable to open surgery. 41 Limbs with post-thrombotic insufficiency have poorer outcomes. 40,42 Concomitant abolition of superficial reflux and lack of deep venous obstruction are predictive of ulcer healing.…”
Section: Subfascial Endoscopic Perforator Vein Surgery (Seps)mentioning
confidence: 72%
See 1 more Smart Citation
“…Piereket al 15 reported an overwhelming 53% of wound infection rate with open perforator ligation whereas no wounds (0%) were infected in the SEPS group. Sybrandy et al compared open perforator ligation with SEPS and concluded that ulcer healing rates and recurrence rates were similar with both the procedures 16 . Therefore, ulcer healing rates achieved with SEPS are equal to that of the open procedure, but the wound complication rate is much lesser with SEPS.…”
Section: The Role Of Subfascial Ligation Of Perforator Veins By Cockementioning
confidence: 99%